The inclusion of sexual and reproductive health services within universal health care through intentional design. Issue 2 (17th December 2020) - Appleford, Gabrielle; RamaRao, Saumya; Bellows, Ben
Abstract: In this paper, we argue that how sexual and reproductive health (SRH) services are included in UHC and health financing matters, and that this has implications for universality and equity. This is a matter of rights, given the differential health risks that women face, including unwanted pregnancy. How traditional vertical SRH services are compensated under UHC also matters and should balance incentives for efficiency with incentives for appropriate provision using the rights-based approach to user-centred care so that risks of sub-optimal outcomes are mitigated. This suggests that as UHC benefits packages are designed, there is need for the SRH community to advocate for more than simple "SRH inclusion". This paper describes a practical approach to integrate quality of SRH care within the UHC agenda using a framework called the "5Ps". The framework emphasises a "systems" and "design" lens as important steps to quality. The framework can be applied at different scales, from the health system to the individual user level. It also pays attention to how financing and resource policies intended to promote UHC may support or undermine the respect, protection and fulfilment of SRH and rights. The framework was originally developed with a specific emphasis on quality provision of family planning. In this paper, we have extended it to cover other SRH services.